AGAMA: ANTARA YANG SAKRAL, YANG PROFAN DAN FENOMENA DESAKRALISASI - Tantri Wulandari (UIN Sunan Kalijaga Yogyakarta, 2014)
Desacralization of religion in social reality is encouraged by two mutually connected things. The first one is the lack ofunderstanding ofreligion. Religion is only understood in certain aspect such as worship, spiritual training and moral messages. Religion is merely considered as alienation of all human problems oflife. When communicated to the rational school of thought of the western ideologies such as materialism, religion become negated because it cannot give the rational arguments in order to seek the solution of the human problem oflife. The second one is social-political and cultural transformationin society covering social-political situation,social-cultural change of society consisting of cultural and family transition and the challenges of modem life. In addition to the problem of criminality, poverty, hunger, under-development, etc., the traditional-religious society of lndonesia is also faced to the foreign ideologies emerging a kind of discomfort within the given order of social values.